Controlling phlebotomine sand flies to prevent canine Leishmania infantum infection: A case of knowing your enemy. (December 2018) - Gálvez, R.; Montoya, A.; Fontal, F.; Martínez De Murguía, L.; Miró, G.
Abstract: Leishmaniosis caused by Leishmania infantum is a widespread zoonotic disease that can be transmitted to animals and humans by their vectors, blood-sucking phlebotomine sand flies. To prevent canine leishmaniosis across the whole Mediterranean region, vector control is essential. Because of phlebotomine breeding sites are diverse, environmental larval controls have limited practical value. Control methods of adults are being evaluated, such as selective baits based on sugar feeding of males and females or Attractive Toxic Sugar Baits (ATSB), and the indoor use of Long-Lasting-Insecticidal Nets (LLINs) treated with permethrin to prevent sand fly bites complementing the Indoor Residual Spraying (IRS) approach suggested by WHO. Although several strategies exist, the best control measure to prevent canine Leishmania infantum is to treat dogs using biocidal topical formulations based on legal insecticides (PTs18) or repellents (PTs19) (as collars, spot-ons and/or sprays) during the period when the vectors are active. This means we need to really know the biology and life cycle of the sand fly vector. According to available data, by mapping ambient temperatures we can already predict high risk areas where vector densities will be higher. In ongoing research, new candidates are emerging to fight against sand flies including natural plant extracts with low impacts on the environment and host animal. Other options in the future could be systemic insecticides to help reduce sand fly populations in high density areas. In parallel, health authorities and professionals involved in animal and public health (veterinarians, physicians, entomologists and epidemiologists) must work together in a One Health approach to minimize Leishmania infection. Veterinarians play a crucial role in liaising between key stake holders and dog owners to ensure the latter act responsibly in using repellents as a preventive measure against sand fly bites. Highlights: The main points highlighted by this review of sand fly control are: Improving the awareness of pet owners of the need for the topical application of repellents on a regular basis as preventive measures against sand fly bite minimizing Leishmania infection is an excellent way to control the infection in dogs. Because of the introduction of infected dogs, the appearance of potential vectors might be a real risk factor of Leishmania infantum dispersion in non-endemic areas; though detecting this new potential vectors must be major concern in these areas. Environmental control measures against sand flies should be inexpensive, sustainable over time and should avoid environmental impacts. The application of the known natural enemies of sand flies as larvicides is limited because of their diversity of breeding places. Further research is needed to evaluate the biological control of sand fly populations by natural enemies. Attractive Toxic Sugar Baits (ATBS) spraying non-flowing green vegetation and within bait stations have been successfully tested for selective control of phlebotomine adults (male and females). Long-lasting Insecticidal Nets (LLINs) could be an important personal protection measure to avoid bites of phlebotomines, and a valuable control measures in large areas where Indoor Residual Spraying (IRS) has a limited success. Promoting health education focused on phlebotomine requirements could help arm the general public with useful information about local vector breeding sites. Predicting vector occurrence through GIS and Remote Sensing in specific regions will provide useful information on which to base the design of appropriate and focused control interventions and when they should be applied.